Physical culture and wellness business in Russia: digital technologies, trends, forecasts - N. V. Filonenko (Путеводитель предпринимателя)
The article actualizes the problem of the health of the Russian population. The impact of the coronavirus pandemic on the development of digital technologies regarding the Russian sports and recreation business is considered. Aspects of the pros and cons of online and offline fitness classes are argued, current trends in the field of health–improving physical culture are outlined, forecasts for the development of the fitness services market in the near future are provided.